2015
DOI: 10.1002/pamm.201510280
|View full text |Cite
|
Sign up to set email alerts
|

Iterated fractional Tikhonov regularization

Abstract: We consider linear operator equations of the formwhere K : X → Y is a compact linear operator between Hilbert spaces X and Y. We assume y to be attainable, i.e., that problem (1) has a solution x † = K † y of minimal norm. Here K † denotes the (Moore-Penrose) generalized inverse operator of K, which is unbounded when K is compact, with infinite dimensional range. Hence problem (1) is ill-posed and has to be regularized in order to compute a numerical solution. We want to approximate the solution x † of the equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Available analyses of iterated Tikhonov regularization only treat the case when L is the identity, that is, the iteration in Equation . However, computed results reported by Huang et al showed that iterative application of Equation with L ≠ I can give better approximations of x † than Equation .…”
Section: Introductionmentioning
confidence: 99%
“…Available analyses of iterated Tikhonov regularization only treat the case when L is the identity, that is, the iteration in Equation . However, computed results reported by Huang et al showed that iterative application of Equation with L ≠ I can give better approximations of x † than Equation .…”
Section: Introductionmentioning
confidence: 99%